Psychometric evaluation of the Coronary Revascularisation Outcome Questionnaire (CROQ) in Norwegian patients admitted to elective coronary angiography and possible percutaneous coronary intervention - Ingvild Nordnes Myrbakk; Oddgeir Friborg; Anne Høye; Terje Steigen; Svein Bergvik (Health and Quality of Life Outcomes, 2022)
Abstract Background The Coronary Revascularisation Outcome Questionnaire (CROQ) measures health-related quality of life and outcome of invasive revascularization procedures such as percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG). The CROQ has not been properly validated in Norwegian patient populations. The aim of this study was to examine the psychometric properties of the Norwegian CROQ in patients admitted to elective coronary angiographic assessment and receiving PCI. Moreover, to examine its discriminative ability to detect disease severity and effects of invasive coronary treatment. Methods The patients (N = 280, M age = 66.9, SD age = 8.91) completed the CROQ, prior to an elective coronary angiography and at one year follow-up. Analyses included internal consistency, floor and ceiling effects, and confirmatory and exploratory factor analyses of the CROQ. Convergent validity was evaluated by comparing CROQ scores with the RAND-12 measure. Sensitivity to treatment was examined by comparing pre-post effect size differences between the PCI treatment and non-treatment group. Results Significant stenosis qualifying for a PCI was detected in 121 (35.1%) patients. The model fit of the original CROQ factor model was inadequate in the PCI group. All but one of the CROQ items demonstrated ceiling effects. The CROQ failed to discriminate between patients’ disease severity prior to the coronary angiography, or improvement in those receiving versus not receiving PCI. Conclusion The present study of the Norwegian version of the CROQ identified serious problems with the factor structure, ceiling effects, and lack of sensitivity for disease severity and effects of invasive treatment. Currently, one cannot recommend the use of CROQ in clinical practice.